MOLP: an easy and interactive way to learn mathematics using online learning portal / Wan Anisha Wan Mohammad, Rafizah Kechil and Azlina Mohd Mydin - Wan Mohammad, Wan Anisha; Kechil, Rafizah; Mohd Mydin, Azlina (Unit Penulisan Dan Penerbitan JSKM, 2022)
Learning mathematics can be done in many ways. However, during this Covid-19 pandemic, the most effective way of learning is through online learning where students can get all the information about the lesson quickly on the internet. Online learning portals can be a useful way to gather all the information and can be accessed easily by the students. Therefore, MOLP was developed as a one-stop center to combine all the interactive materials together. It can be an easy and interactive way to learn mathematics using online learning portal. MOLP was specifically developed for Pre-Commerce students who is learning Intensive Mathematics 1. A survey has been conducted to understand the student’s limitations with the distribution of the current learning materials and their satisfaction in using MOLP. All the respondents agree that MOLP can help them in their studies, and they fully recommend MOLP to their friends.